2020
DOI: 10.1038/s41440-020-0455-8
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of coronaviruses with ACE2, angiotensin II, and RAS inhibitors—lessons from available evidence and insights into COVID-19

Abstract: The rapid spread of a novel coronavirus,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
345
0
26

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 390 publications
(380 citation statements)
references
References 42 publications
9
345
0
26
Order By: Relevance
“…Another study has reported lower risk of all‐cause mortality among COVID‐19‐hospitalized patients receiving RAAS inhibitors 21 . Other studies have concluded that there is no clinical or experimental evidence supporting that ARBs and ACEIs either augment the susceptibility to SARS‐CoV‐2or aggravate the severity and outcomes of COVID‐19 at present 22 . Indeed, a recent review has concluded that ACEIs and ARBs may be associated with lower incidence and/or improved outcome in patients with lower respiratory tract infections 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study has reported lower risk of all‐cause mortality among COVID‐19‐hospitalized patients receiving RAAS inhibitors 21 . Other studies have concluded that there is no clinical or experimental evidence supporting that ARBs and ACEIs either augment the susceptibility to SARS‐CoV‐2or aggravate the severity and outcomes of COVID‐19 at present 22 . Indeed, a recent review has concluded that ACEIs and ARBs may be associated with lower incidence and/or improved outcome in patients with lower respiratory tract infections 20 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the Spike (S) protein of SARS-CoV-2 binds with high a nity to human ACE2, and before SARS-CoV-2's entry into the cells [16][17][18], the S protein is subjected to a priming process via serine protease TMPRSS2 in order to permit the attachment of viral particles to ACE2 and thus on cell surface [19,20]. Therefore, SARS-CoV-2 can directly attack cardiac muscle cells through this pathway [21][22][23]. This entry mechanism is con rmed by the fact that TMPRSS2 inhibition or TMPRSS2-KO mice show both decreased, though not abolished, S protein priming, and reduced viral entry, spread, as well as, in ammatory chemokine and cytokine release [19].…”
Section: Discussionmentioning
confidence: 99%
“…With so many pieces of data missing, the need for vigorous clinical studies guided by physiology-based questions and hypotheses are most urgent. Such a question includes the continuation or even introduction, rather than cessation of RAS inhibitors in patients infected by SARS-CoV-2 ( Kai and Kai, 2020 ), or can we inhibit binding of SARS spike proteins to ACE2, for instance by antibodies, without hampering its catalytic capacities to generate Ang 1-7? Is there a role for the application of Ang 1-7 or MasR agonists or for the administration of intravenous sACE2, with an available proof of concept for such postulated approaches ( Yang et al, 2014 ; Hemnes et al, 2018 )?…”
Section: Knowledge Gaps: the Missing Pieces In The Puzzlementioning
confidence: 99%